Induction of interleukin-1β by mouse mammary tumor irradiation promotes triple negative breast cancer cells invasion and metastasis development. (4th May 2017) - Bouchard, Gina; Therriault, Hélène; Bujold, Rachel; Saucier, Caroline; Paquette, Benoit
Abstract: Purpose: Radiotherapy increases the level of inflammatory cytokines, some of which are known to promote metastasis. In a mouse model of triple negative breast cancer (TNBC), we determined whether irradiation of the mammary tumor increases the level of key cytokines and favors the development of lung metastases. Materials and methods: D2A1 TNBC cells were implanted in the mammary glands of a Balb/c mouse and then 7 days old tumors were irradiated (4 × 6 Gy). The cytokines IL-1β, IL-4, IL-6, IL-10, IL-17 and MIP-2 were quantified in plasma before, midway and after irradiation. The effect of tumor irradiation on the invasion of cancer cells, the number of circulating tumor cells (CTC) and lung metastases were also measured. Results: TNBC tumor irradiation significantly increased the plasma level of IL-1β, which was associated with a greater number of CTC (3.5-fold) and lung metastases (2.3-fold), compared to sham-irradiated animals. Enhancement of D2A1 cell invasion in mammary gland was associated with an increase of the matrix metalloproteinases-2 and -9 activity (MMP-2, -9). The ability of IL-1β to stimulate the invasiveness of irradiated D2A1 cells was confirmed by in vitro invasion chamber assays. Conclusion: Irradiation targeting a D2A1 tumor and its microenvironment increased the level of the inflammatory cytokine IL-1β and was associated with the promotion of cancer cell invasion and lung metastasis development.